The effects of digitalisation on health and social care work: a qualitative descriptive study of the perceptions of professionals and managers - Anu-Marja Kaihlanen; Elina Laukka; Janna Nadav; Johanna Närvänen; Petra Saukkonen; Juha Koivisto; Tarja Heponiemi (BMC, 2023)
Abstract Background Today, digitalisation is strongly present in health and social care, and it increasingly affects the organisation of work, work requirements, tasks and tools. Due to the constant change in work, up-to-date knowledge is needed about these micro-level effects of digitalisation and how professionals experience the effects in their work. Furthermore, even though managers play a key role in implementing new digital services, their perceptions of the effects of digitalisation and whether they match the views of professionals remain unknown. This study examined how health and social care professionals and managers perceive the effects of digitalisation on the work of professionals. Methods We used a qualitative approach and conducted eight semi-structured focus group interviews with health and social care professionals (n = 30) and 21 individual interviews with managers in 2020 in four health centres in Finland. The qualitative content analysis included both an inductive and a deductive approach. Results Digitalisation was perceived to have changed professionals' 1) workload and pace, 2) the field and nature of work, 3) work community communication and interaction, and 4) information flow and security. Both professionals and managers identified effects such as accelerated work, reduction in workload, constant learning of technical skills, complicated work due to vulnerable information systems, and reduction in face-to-face encounters. However, managers did not bring up all the effects that professionals considered important, such as the creation of new work tasks, increased and duplicated work, or insufficient time to get acquainted with the systems. Conclusions The findings suggest that some of the effects of digitalisation on professionals' work and changes in the workplace may receive too little or no recognition from managers. This increases the risk that the potential negative effects may be overlooked and that managers will adopt systems that do not support the work of professionals. To reach a common understanding of the effects of digitalisation, continuous discussions between employees and different management levels are required. This contributes to professionals' well-being and adaptation to changes, as well as the provision of quality health and social services.